STUDI KASUS: KEMAMPUAN MENGINGAT PESERTA DIDIK KELAS 2 SDN PONTANG 2 - Sri Ismawati; Desty Endrawati Subroto; Ifdah, Ifdah (Sindoro: Cendikia Pendidikan, 2025)
This research analyzes the extraordinary memory abilities demonstrated by 11 out of 21 grade 2 students at SDN PONTANG 2. They are able to memorize country names, colors and flag symbols with high accuracy. This phenomenon is interesting because it is rarely found in children his age who are usually still learning basic skills such as reading and writing. A qualitative approach with a case study method was used to explore factors supporting students’ memory abilities, such as the role of the learning environment, teaching strategies, and family support. Data was collected through in-depth interviews, observation and documentation with students and teachers. Thematic analysis identified patterns and themes related to memory development. The results show that interactive teaching methods, such as visual media and educational games, are very effective in improving students’ abilities. However, challenges such as lack of cognitive stimulation at home and limited school facilities remain obstacles.